Empatia e percezione estetica. Lo "spirito della musica" come principio unificatore (Materiali di Estetica. Terza serie, 2025)
The two aspects that constitute works of art: representation and the rhythmic-musical principle, have both been considered by neuroscience in reference to empathy, as mimetic forms that allow psychophysical identification with the other. Nietzsche problematized these two aspects by bringing out, with the categories of Apollonian and Dionysian, principles of artistic expression, which in their interaction characterize the different genres of art. If the Apollonian principle, in the light of studies on empathy, can be referred mainly to identification with the representation of human figures with an emotional involvement, the "spirit of music", in the light of Nietzsche's problematization of the Dionysian principle, takes on ambiguous characteristics, also referable to different aspects of empathy. Among these, rhythmic ecstasy, whose depersonalizing involvement has an effect of dissolving subjectivity. Opposite genres of empathy that generally interpenetrate and interact in the arts in the realization of beauty. Beauty therefore takes on this ambivalence with respect to empathy: the subjective involvement of representation, in tension with the opposing Dionysian force, a transfiguring cosmic involvement.
Keywords: Aesthetic perception; beauty; Apollonian and Dionysian; empathy